Magnetic porous biochar with nanostructure surface derived from penicillin fermentation dregs pyrolysis with K2FeO4 activation: Characterization and application in penicillin adsorption. (May 2021) - Wang, Qiuju; Zhang, Zhao; Xu, Guoren; Li, Guibai
Highlights: Magnetic biochars (MCHCl, MCHAc ) were prepared from dregs by K2 FeO4 activation. MCHCl and MCHAc have high BET surface areas of 672 and 735 m 2 /g, respectively. MCHCl and MCHAc had saturation magnetizations of 75.29 and 42.45 emu/g, respectively. MCHCl had nano sticks of ~80 nm & MCHAc had petal-like slice of ~30 nm on surfaces. Maximum adsorption capacities of penicillin on MCHCl and MCHAc were 196 & 322 mg/g. Abstract: Magnetic porous biochars (MCHCl, MCHAc ) with nanostructure on surfaces were prepared from penicillin fermentation dregs by pyrolysis with K2 FeO4 activation and used in penicillin adsorption. MCHCl and MCHAc had high BET surface areas of 672 and 735 m 2 /g, respectively; mainly be attributed to the activation of K2 FeO4 as well as acid pickling. Saturation magnetizations of MCHCl and MCHAc were 75.29 and 42.45 emu/g, respectively; the magnetism was mainly derived from the Fe3 O4 and Fe3 C in magnetic biochars. MCHCl had nano sticks of ~ 80 nm and MCHAc had petal-like slice of ~ 30 nm on surfaces. The maximum adsorption capacities of penicillin on MCHCl and MCHAc were 196 and 322 mg/g at 308 K, respectively. The adsorptions of penicillin on MCHCl and MCHAc were consistent with pseudo primary kinetics and the Langmuir adsorption isotherm model, and thermodynamic analysis indicated that the adsorption mechanism included physical and chemical adsorption.